Benefits of combinative application of probiotic, enterocin M-producing strain Enterococcus faecium AL41 and Eleutherococcus senticosus in rabbits - Lauková, Andrea; Simonová, Monika Pogány; Chrastinová, Ľubica; Plachá, Iveta; Čobanová, Klaudia; Formelová, Zuzana; Chrenková, Mária; Ondruška, Ľubomír; Strompfová, Viola (Folia microbiologica, 2016)
This study presents the effects of the probiotic and enterocin M-producing strain Enterococcus faecium AL41 on microbiota, phagocytic activity (PA), oxidative stress, performance and biochemical parameters when applied individually or in combination with Eleutherococcus senticosus in rabbits. The novelty of the study lies in the use of our non-rabbit-derived strain (AL41 = CCM8558) which produces new enterocin M. Ninety-six post-weaned rabbits (Hyplus breed) aged 5 weeks were divided into three experimental groups, 24 in each: E. senticosus (ES, 30 g/100 kg) in feed, E. faecium AL41 (10(9) CFU/mL marked by rifampicin to differentiate it from other enterococci) in water, and ES + AL. AL41 colonized sufficiently in rabbits to reduce coliforms, staphylococci, pseudomonads and clostridia. Slight decrease in bacteria was also found in the caecum and appendix. Phagocytic activity was significantly increased in the experimental groups compared to the control group (CG) (p < 0.001; p < 0.05). Applications did not evoke oxidative stress. Biochemical parameters in blood and caecal organic acids were slightly influenced. Average daily weight gain was slightly higher in ES and AL + ES. Combinative application of E. faecium with E. senticosus can be beneficial in rabbits. AL41 strain alone and in combination with ES produced reduction in spoilage bacteria; the highest stimulation of PA was in the AL41 + ES group.
Keywords: Feces; Male; Eleutherococcus; probiotika; Gastrointestinal Microbiome; eleuterokok; mužské pohlaví; střevní mikroflóra; králíci; Enterococcus faecium; přemostěné cyklické sloučeniny; Animals; ženské pohlaví; Bridged-Ring Compounds; zvířata; Rabbits; Probiotics; Female; feces